Environmental dimorphism of the incidence of significant correlations between feet and body trunk parameters among 14-18-year-old adolescents - Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2018)
Introduction. The analysis of correlations between selected parameters of body trunk and feet in 14-18-year-old adolescents revealed their incidental and random character making it impossible to prove any regularities or dependencies between the investigated parameters. Their concomitance can only be determined. Material and method. The study conducted with the group of adolescents aged 14 to 18 years enabled to record 2 445 observations including 1 167 in the urban environment and 1278 in the rural environment with regard to the measurement of the 87 parameters describing body trunk and feet. The station for measurement of the selected parameters using the photogrammetric method consisted of a computer, a card, software, a display monitor, a printer and a projection-reception device with a camera. Conclusions 1. The prevalence of significant correlations between the parameters of body trunk and feet differentiating the urban environment from the rural one is larger. The parameters of the sagittal plane and, to a lesser extent, of the frontal plane, differentiate the urban environment, and only frontal parameters differentiate the rural environment. 2. The prevalence of significant correlations between feet parameters significantly correlating with the parameters of body trunk and differentiating the urban environment from the rural one is bigger. These are morphological features which characterize the longitudinal arch of feet and disorders of the great toe location. The parameters which diversify the rural environment are the features describing the transverse and longitudinal arch.